2005
DOI: 10.1161/01.str.0000150494.91762.70
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-Lowering Treatment With Folic Acid, Cobalamin, and Pyridoxine Does Not Reduce Blood Markers of Inflammation, Endothelial Dysfunction, or Hypercoagulability in Patients With Previous Transient Ischemic Attack or Stroke

Abstract: Background and Purpose-Epidemiological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 6 publications
8
47
0
2
Order By: Relevance
“…Four studies [9,[12][13][14] showed differences in blood concentrations of Hcy between subjects consuming diets high in fruits and vegetables or dietary (natural occurring) folate and subjects consuming their usual diet or diets low in fruits and vegetables or in folate, whereas three studies [11,15,16] did not. It may be noted that, even if Hcy levels can be lowered by increasing folate intake, its effect on the risk of cardiovascular disease is currently under debate, because in recent trials reductions in plasma Hcy levels had no favorable effects on blood markers of inflammation, endothelial dysfunction, or hypercoagubility [5,6]. This suggests that Hcy is just a marker of vascular risk and not a causal factor or that high Hcy levels may cause cardiovascular disease through mechanisms other than those mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [9,[12][13][14] showed differences in blood concentrations of Hcy between subjects consuming diets high in fruits and vegetables or dietary (natural occurring) folate and subjects consuming their usual diet or diets low in fruits and vegetables or in folate, whereas three studies [11,15,16] did not. It may be noted that, even if Hcy levels can be lowered by increasing folate intake, its effect on the risk of cardiovascular disease is currently under debate, because in recent trials reductions in plasma Hcy levels had no favorable effects on blood markers of inflammation, endothelial dysfunction, or hypercoagubility [5,6]. This suggests that Hcy is just a marker of vascular risk and not a causal factor or that high Hcy levels may cause cardiovascular disease through mechanisms other than those mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…A high folate intake by women of child-bearing age is associated with a lower risk of neural tube defects in their newborn children [1]. Moreover, increasing the intake of folate has the potential of lowering high blood concentrations of homocysteine (Hcy), which is associated with a risk of cardiovascular disease [2][3][4] although evidence for a causal relation is lacking; it has been suggested that Hcy may only be a marker but not a cause of increased vascular disease risk [5,6]. A meta-analysis of 12 randomized controlled trials showed that daily supplementation with folic acid (the form of folate found in vitamin supplements and fortified food) in the range of 0.5-5 mg and with about 0.5 mg of vitamin B12, another determinant of Hcy in blood [7] would be expected to decrease blood Hcy concentrations in Western populations by approximately 25% to 33% [8].…”
Section: Introductionmentioning
confidence: 99%
“…4 However, so far, HCY-lowering trials in persons at high vascular risk have not shown that this strategy reduces vascular risk, [7][8][9] although one of these trials that did not meet its primary end point found that significantly fewer patients who received the HCY-lowering intervention experienced a stroke. 9 It must, however, be pointed out that these trials had a subject mean age of 66 to 68 years, and although other trials are ongoing, 10 it is possible that relatively younger adults may benefit more from such treatment. 11,12 Indeed, a detailed review of the HOPE-2 trial data and reanalysis of the VISP trial restricted to patients capable of responding to vitamin therapy indicated that higher doses of vitamin B12 and possibly novel methods of reducing total HCY besides routine vitamin therapy could potentially reduce the risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…В последующем было проведено исследование VITATOPS, в результате которого было установлено, что назначение 285 пациентам, перенесшим ишемический инсульт или ТИА, препаратов цианокобаламина (0,5 мг), пиридоксина (25 мг) и фолиевой кислоты (2 мг) ежедневно на протяжении 6 мес привело к до-стоверному снижению концентрации в крови гомоци-стеина [22]. Одновременно в группе больных, получав-ших лечение, наблюдалось достоверно меньшее количество ТИА.…”
Section: гипергомоцистеинемияunclassified